CFD Modeling for Estimating Consequences of Liquid Hydrogen Release Transported by Road Tankers through Tunnels - Ciro Caliendo; Gianluca Genovese; Frank Markert; Paola Russo (Advances in Civil Engineering)
Among the new energy carriers targeted at mitigating greenhouse gas emissions, the use of hydrogen is likely to experience substantial growth in the future. In this context, the transport of liquid hydrogen by means of road tankers might represent the most cost-effective option for delivery over long distances in the short-term perspective. Liquid hydrogen, however, entails non-negligible risks, especially in confined spaces like road tunnels. An accidental release might form a flammable hydrogen cloud that might deflagrate or even detonate. Nevertheless, the consequences on users in the event of accidental leakage of liquid hydrogen from road tankers have not yet been sufficiently investigated. Therefore, this paper regards specific 3D computational fluid dynamics models to quantify the effects due to both liquid hydrogen release and potential deflagration and/or detonation within road tunnels. The proposed models were calibrated and subsequently validated with the findings of certain literature studies. Since the effects on tunnel users might be influenced, apart from tunnel geometry, by the type of ventilation and traffic flow, tunnel environmental conditions involving natural or mechanical ventilation, as well as off or peak traffic hours (i.e., night or day traffic) were more especially investigated. The results of simulations, in terms of overpressures generated from a potential hydrogen explosion, showed benefits due to mechanical ventilation and/or under lower traffic flows. By providing additional knowledge to the field of hydrogen safety, this study might help tunnel management agencies to make improved management and/or traffic control strategies (e.g., decisions on whether or not mechanical ventilation should be installed also in tunnels less than 1,000 m long and/or allowing the transit of road tankers transporting liquid hydrogen only at night rather than day).